Analisa Kuantitas Dan Kualitas Airtanah Di Kecamatan Kubu Kabupaten Karangasem Provinsi Bali - Wijayanti, Putu Ratih; Sholichin, Moh.; Sisinggih, Dian (Fakultas Teknik, Universitas Brawijaya, 2013)
Kubu Subdistrict is located at Karangasem District and belongs to Tejakula Groundwater Basin. It is droughty region with few rainfalls compared to other region. The purpose of this research is to determine the quantity and the quality of groundwater for agriculture. The analysis of groundwater quantity is by applying the pumping test. The pumping test is divided into two stages, which are well test and aquifer test. Result of well test at 7 (seven) production wells is obtaining the optimum discharge ranging from 10.107 liter/second to 18.604 liter/second. Aquifer test analysis involves the first stage is to determine the type of flow from each well that is steady or unsteady flows, and then determine the method that will be used based on the type of flow and type of aquifer. In determining the type of flow is obtained steady flow types for 3 (three) wells and unsteady flow types for 4 (four) wells. Groundwater quality analysis is conducted by Aquachem software version 2011.1 (demo version). Based on the analysis of groundwater quality, groundwater is containing low and medium Sodium and have high and very high salinity.Keywords: quantity, quality, groundwater, wells test, aquifer test, Sodium.